Subjectively Perceived Importance of Education by University Students at the Beginning of Their Studies - Radmila Burkovičová (Journal of Elementary Education, 2022)
The article investigates students perception of the importance of education and its rationale at the beginning of their studies. Fifty-seven students from the bachelor’s programme Teacher Training for Kindergarten from 2018/2019 to 2021/2022 participated. The sampling was based on convenience. A qualitative approach was used through open verbal statements transcribed into a text. The individual importance of education to students at the beginning of the first semester and their personal justifications for the importance of education were identified, representing several categories. We found the following dimensions for the categories of the meaning of education (personal goal category) and personal definition of education (categories: association with context; from individual to society; on the background of historical development; personality development and evolution; essence; mode of acquisition; value; through the lens of the present; Dionysian conception; general overview; confused definitions).